2020
DOI: 10.3389/fgene.2020.00649
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the First W-Specific Protein-Coding Gene for Sex Identification in Helicoverpa armigera

Abstract: Helicoverpa armigera is a globally-important crop pest with a WZ (female)/ZZ (male) sex chromosome system. The absence of discernible sexual dimorphism in its egg and larval stages makes it impossible to address any sex-related theoretical and applied questions before pupation unless a W-specific sequence marker is available for sex diagnosis. To this end, we used one pair of morphologically pre-sexed pupae to PCR-screen 17 non-transposon transcripts selected from 4855 W-linked candidate reads identified by ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…This is because the femalespecific W chromosome in Lepidoptera is packed with transposons that can be transcribed into non-coding RNAs [6,[49][50][51]. Our recent characterization of the first W-specific proteincoding gene GUW1 from H. armigera [35] suggests that the W-specific GUW1 may function as the primary signal to minimize HaMasc expression in female cotton bollworms. Further experiments are required to examine these two possibilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because the femalespecific W chromosome in Lepidoptera is packed with transposons that can be transcribed into non-coding RNAs [6,[49][50][51]. Our recent characterization of the first W-specific proteincoding gene GUW1 from H. armigera [35] suggests that the W-specific GUW1 may function as the primary signal to minimize HaMasc expression in female cotton bollworms. Further experiments are required to examine these two possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic PCR gel analysis showed that the band intensity of HaMasc amplified from male (AA + ZZ = 2 copies of each autosome + 2 copies of Z chromosome) pupa was roughly two times of that from female (AA + ZW = 2 copies of each autosome + 1 copy of Z chromosome/1 copy of W chromosome) pupa, whereas the band intensity of the autosomal gene EF-1α was equal between the male and female pupa (Figure 4A). Further genomic qPCR analysis revealed that the male copy/female copy ratio was 0.0023 for the W chromosome gene GUW1 [35], 1.00 for the autosomal gene EF-1α, 0.98 for the autosomal gene β-actin, and 2.32 for HaMasc (Figure 4B). These data confirm that the HaMasc gene is located on Z chromosome.…”
Section: Chromosomal Assignment Of Hamasc To Z Chromosomementioning
confidence: 99%
“…Another sex chromosome (W) was identified according to the criterion that mapped reads are completely absent in male but in theory drop to half in females. In fact, the mean sequencing coverage of W in males is not completely absent due to the high repeat content of Lepidoptera W chromosomes (Abe et al, 2005; Deng et al, 2020). Basic genomic features including sequencing coverage, coverage ratio between females and males, GC content, and gene density were displayed using circos version 0.69–8 (Krzywinski et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, we defined this chromosome as the Z chromosome. However, the W chromosome was not properly assembled in this study, possibly due to the complex structure and high repetitive content widely found on lepidopteran W chromosomes (Abe et al, 2005;Dalíková et al, 2017;Deng et al, 2020). Alternatively, we characterized 40 scaffolds comprising ~3.9 Mb, which showed extreme sequencing coverage bias in females (ZW) as W candidate scaffolds (Figure S3, Table S4).…”
Section: Ta B L E 1 Statistics Of the Ectropis Grisescens Assembly In Comparison With Related Speciesmentioning
confidence: 99%
See 1 more Smart Citation